Relationship between Human and Animal in Kate DiCamillo The Magician's Elephant - Syafira Hardina Chairani; Masulah Masulah; Ari Setyorini (Tell : Teaching of English Language and Literature Journal, 2019)
This study aimed to analyse the relationship between human and animal in Kate DiCamillo’s novel entitled The Magician’s Elephant. This study analyzed how the people in The Magician’s Elephant treat the animal. From the analysis in the research, the researcher found the disharmony of the relationship between humans and animals in the novel. This novel is very anthropocentric, where the people in it do not build good relations with animal, including exploiting and treating animal improperly. Ecocriticism opposes excessive exploitation of nature. All animals in the world have their own rights to life no less certainly as human do. Ecocriticism believes that animals could feel like the human in the world, aware of the world, also aware of what happens to them. Include their bodies, their freedom, even their lives. The researcher used ecocritcism theory to support this research. Qualitative descriptive is used as the research method in this research. Based on the analysis the reasearcher conclude that The Magician’s Elephant have the animal right issues, where humans ought to establish good relations with nature, especially animals